TOKA-TOKI MELAYU, KUANTAN SINGINGI, RIAU: PENUTUR, WAKTU, BAHASA, DAN FUNGSI - Yulita Fitriana (Balai Bahasa Provinsi Riau, 2013)
There is inadequate number of research on “toka-toki” of Kuantan Singingi at the present time. In consequence, there is insufficient extensive knowledge about the speakers, the time of usage, the language used, and the function of the “toka-toki”. In this study, those elements become the object of the research analysis. The method used in the analysis is qualitative descriptive method. The data was obtained from the field and also literature. The implementation phase of this study were (1) collecting data, namely by asking about the desired data related to the speaker, time, language, and “toka-toki” function to the informant, (2) the phase of analyzing the data, and (3) the phase of making conclusion. From this study, it was concluded that the speakers of “toka–toki” in the Kuantan Singingi are not limited to the age levels, the social levels, and education levels. Actually there is no specific time of the implementation of this “toka-toki”. However, the game is often found when children play, after “mengaji” (reading Koran), or going to sleep in “surau”, drying rice, and looking for lice. The next conclusion, the question words used in implementing “toka-toki” are ‘siapo’; ‘sapo’ 'who' and ‘apo’ 'what' with some variations such as “apo ru”, “apo lo ru”, “apo tu”, “apo jie kilen”. In addition to the use of question words, “toka-toki” of Kuantan Singingi can use literal meaning and metaphorical meaning. Meanwhile, the function of the “toka-toki” Kuantan Singingi is to sharpen the mind and to deliver education and entertainment, and to tease others Penelitian mengenai toka-toki Kuantan Singingi belum banyak dilakukan. Hal tersebut menyebabkan pengetahuan mengenai penutur, waktu penggunaan, bahasa yang digunakan, dan fungsi toka-toki yang hidup di dalam masyarakat Kabupaten Kuantan Singingi juga masih minim. Di dalam penelitian ini, penutur, waktu, bahasa, dan fungsi toka-toki inilah yang dijadikan objek penelitian. Metode yang digunakan adalah kualitatif-deskriptif. Data didapat dari lapangan dan juga kepustakaan. Tahap pelaksanaan penelitian ini adalah (1) pengumpulan data, yaitu dengan bertanya mengenai data yang diinginkan berkaitan dengan penutur, waktu, bahasa, dan fungsi toka-toki kepada informan, (2) tahap penganalisisan data, dan (3) tahap pengambilan simpulan. Dari penelitian ini, disimpulkan bahwa penutur toka-toki di daerah Kuantan Singingi tidak terbatas pada tingkatan usia, tingkatan sosial, dan tingkatan pendidikan tertentu. Sebenarnya tidak ada waktu khusus pelaksanaan tokatoki ini. Akan tetapi, permainan ini sering dijumpai pada saat anak-anak bermain, sesudah mengaji, atau akan tidur di surau, menjemur padi, dan mencari kutu rambut. Simpulan selanjutnya, kata tanya yang dipergunakan di dalam bertoka-toki adalah kata siapo; sapo’siapa’ dan apo ‘apa’ dengan variasi apo ru, apo lo ru, apo tu, apo jie kilen. Selain penggunaan kata tanya, toka-toki Kuantan Singingi dapat menggunakan bahasa yang literal (harfiah) dan metaforis (kiasan). Sementara itu, fungsi dari toka-toki Kuantan Singingi adalah mengasah pikiran dan menyampaikan pendidikan, hiburan, dan menggoda orang lain.